A planar dithiafulvene based sensitizer forming J-aggregates on TiO2 photoanode to enhance the performance of dye-sensitized solar cells. (January 2017) - Cheng, Jun; Zhang, Fang; Li, Ke; Li, Jie; Lu, Xiaoqing; Zheng, Jingxia; Guo, Kunpeng; Yang, Shihe; Dong, Qingchen
Abstract: A newly planar dithiafulvene sensitizer (DTF-C4 ) trending to form J -aggregates on the surface of mesoporous TiO2 by simply rinsing with a poor solvent acetonitrile was synthesized. We further show that the self-assembled J -aggregates optimized the TiO2 surface utilization, enhanced the light harvesting ability by broadening and red-shifting the absorption, and suppressed the electron recombination, thereby significantly promoting the solar cell efficiency. Compared to the photoanode surface modified withDTF-C4 and the classical coadsorbent chenodeoxycholic acid (CDCA), the DSC based theDTF-C4 compact J -aggregates exhibited a dramatically improved performance without the loss of adsorbed dyes, uplifting the power conversion efficiency from 4.68% to 7.48% alongside with a high open-circuit voltage of above 850 mV, which is higher than that of the commercial N719-based cell (770 mv). Graphical abstract: The self-assembled J -aggregates of a newly synthesized planar dithiafulvene sensitizer optimized the TiO2 /dye interface, uplifting the power conversion efficiency from 4.68% to 7.48% alongside with a high open-circuit voltage of above 850 mV. Highlights: A newly planar geometry of dithiafulvene sensitizerDTF-C4 was synthesized. Formation of J -aggregates ofDTF-C4 on TiO2 by rinsing with a poor solvent acetonitrile. Increasing the J -aggregates ofDTF-C4 on TiO2 lead to uplift PCE to 7.48% and V oc above 850 mv. J -aggregates ofDTF-C4 enhanced light harvesting ability and retarded electron recombination.